When Does a Firm Fail to Walk the Talk? Decoupling in International Expansion - Xu, Kai; Shi, Wei; Zhao, Jing; Chen, Xuanyu (Journal of Management Studies, 2025)
AbstractNeo‐institutional theory predicts that when adaptations to institutional pressures contradict a firm's efficiency needs, decoupling may arise. This study systematically investigates the drivers of heterogeneous decoupling in the context of international expansion. We propose that specific configurations – awareness of peers’ decoupling, a strong motivation to obtain legitimacy through ceremonial conformity, and a weak capability to couple stated policies with practices – will lead to a high occurrence of decoupling. An empirical analysis of 8918 annual reports of 1974 Chinese‐listed companies from the period 2013–17 suggests that the ‘Go Global’ initiative undertaken by the Chinese government has created high institutional pressure for all Chinese firms to expand globally. However, when the implementation of that move is perceived as too costly or risky for a firm, the firm is likely to choose to decouple its international expansion from its stated commitment to expand under certain configurations of awareness, motivation, and capability conditions. Our theory and empirical findings extend decoupling research and international business research by providing a holistic configurational analysis of firms’ decoupling in an international expansion context.